Steering exciton dissociation and charge migration in green synthetic oxygen-substituted ultrathin porous graphitic carbon nitride for boosted photocatalytic reactive oxygen species generation - Guo, Hai; Niu, Cheng-Gang; Feng, Cheng-Yang; Liang, Chao; Zhang, Lei; Wen, Xiao-Ju; Yang, Yang; Liu, Hui-Yun; Li, Lu; Lin, Li-Shen (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Novel OCN-24-550 photocatalyst was prepared by a green strategy.•OCN-24-550 exhibits outstanding photocatalytic performance for ROS generation.•Ultrathin porous structure and oxygen-substitution boost exciton dissociation.•This work provides guidance for the development of g-C3N4-based photocatalyst. Light-driven reactive oxygen species (ROS) generation from molecular oxygen activation is normally recognized as an effective route for environmental pollutants removal. Herein, oxygen-substituted ultrathin porous graphitic carbon nitride (g-C3N4) nanosheets are prepared through a two-step hydrothermal-recalcination treatment of bulk g-C3N4 (BCN), and it is found that the obtained samples display enhanced ROS generation, as reflected by the removal of oxytetracycline hydrochloride (OTC). When stimulated by visible light, about 85.76% of OTC can be removed by the optimal sample (OCN-24-550) within 120 min, which is obviously higher than that of bulk g-C3N4 by a factor of 4.99. Meanwhile, nitroblue tetrazolium (NBT) transformation and H2O2 generation also indicate that the OCN-24-550 possess the highest reactivity, which can produce 47.25 μM of H2O2 and 9.07 × 10−10 M of the steady-state O2− during the reaction. The enhanced photocatalytic performance of OCN-24-550 is attributed to the synergistic effect of ultrathin porous structure and heteroatom O substitution. Specifically, the ultrathin porous structure can enlarge the surface area and then facilitate the diffusion of reactant, while the O substitution can optimize the electronic structure by creating a local electronic polarization effect, as confirmed by density functional theory (DFT) calculations, and thus result in a boosted exciton dissociation and accelerated charge migration. This work not only presents a comprehensive insight into g-C3N4-based reaction system from exciton and charge carrier, but also provides a meaningful guidance for exploring novel photocatalytic wastewater treatment devices from a more environment-friendly perspective.